Republic of Mozambique : Fifth Review Under The Policy Support Instrument And Request For Modification Of Assessment Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
Despite the difficult global environment, economic growth in Mozambique has remained buoyant. Inflation has come down more rapidly than anticipated. Foreign direct investment in the natural resource sector has resulted in rapid import growth. The contribution of coal production and exports and the implementation of large infrastructure projects are projected to boost economic growth. However, capacity building is urgently needed for the country to secure full benefits from an imminent natural resource boom. New mining and hydrocarbon framework laws have also been prepared.